Influence of Shear Connector Size on Ultimate Strength in Composite Construction with Cold-Formed Steel Channel Lipped Section - Tahir, Mahmood Md; Lawan, Mustapha Muhammad; Saggaff, Anis; Mirza, Jahangir (Review of Industrial Engineering Letters, 2016)
In conventional composite construction for buildings and bridges, Hot-Rolled Steel (HRS) section is well known to be used. The composite action is usually achieved by using conventional headed stud shear connectors. However, for Cold-Formed Steel (CFS) section, the use of headed stud shear connectors is not feasible as the section is very thin and incapable to be weld. Therefore, a suitable shear connection system of bolt and nut is proposed in this study by varying the size of the bolted shear connectors. This paper presents the prospect of using a bolt and nut as shear connector that could be well-suited with CFS section when integrated in Self-Compacting Concrete (SCC). The experimental test comprised of push-out and was conducted to determine the strength and ductility of the proposed bolted shear connectors as used in composite construction. Eight push-out test specimens of bolted shear connector size consist of M12, M14 and M16 of grade 8.8 were fabricated and tested to failure. The experimental results show that the bolted shear connectors used to possess good shear resistance capacity. Influence of varying the size of the bolted shear connectors was investigated. The results show that the size of bolted shear connectors influenced the ultimate strength capacity of the shear connectors significantly.